DIGITALISASI MEDIA PEMBELAJARAN PRAKTIKUM FISIKA DASAR - Syamsuriwal; Jarnawi, Muhammad; Syarif, Muh. (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The way students learn during the COVID-19 pandemic has undergone a very significant change. Online learning has become a new method of teaching students. Therefore, lecturers must quickly adapt to face this condition. This study aims to determine the feasibility of the product developed, namely video tutorials and basic physics practicum e-modules by validators and perceptions of students. This type of research is research and development, R & D (Research and Development) using the 4-D model. The respondents of this study were 150 odd semester students for the 2021/2022 academic year who programmed basic physics courses. The research instrument is a media expert validation sheet and materials for e-modules and video tutorials as well as student perception instruments. Prior to the CoA test, the developed e-modules and video tutorials were tested for validity and reliability. The results of the validity show that both are in the very valid category and the reliability is 0.8. The results of students' perceptions of video tutorials for the three assessment indicators, namely efficient, effective, and attractive are 83.1%. This shows that the developed e-modules and practicum tutorial videos are very good and suitable for use in basic physics practicum activities conducted online.